Functional cookies made from black rice for oxidative stress control in overage and obesity adolescents - Wiwit Estuti; Kunaepah Uun; Lia Nurcahyani (AcTion: Aceh Nutrition Journal, 2025)
Health problems in Indonesia generally occur because of the unhealthy lifestyles of adolescents or sedentary lifestyles. The most common cases are health problems, such as obesity and overweight. This study aimed to measure the effect of providing functional cookies on controlling oxidative stress in obese adolescents, determine the compliance of cookie consumption by subjects, and conduct consumer tests. The study used an experimental design conducted from August to September 2022 at SMP Negeri 7 Cirebon City. The participants were 24 adolescents aged 13-15 years. Data were collected using questionnaires and analyzed for malondialdehyde (MDA) and Superoxide Dismutase (SOD) levels in the blood serum. Data analysis was performed using the Mann-Whitney U test and Pearson correlation test at 95% CI. The results showed that the provision of functional cookies significantly (p<0,05) reduced serum malondialdehyde (MDA) levels in overweight and normal adolescents (p = 0,017). Superoxide dismutase (SOD) enzyme activity had no effect on overweight/obese and normal adolescents after providing functional cookies. In conclusion, providing functional cookies can reduce MDA levels in obese and normal adolescents (p = 0,017) but had no effect on SOD enzyme activity. The adherence to cookie consumption and consumer test results support its potential in controlling oxidative stress in adolescents.